2008
DOI: 10.1007/s00167-008-0535-9
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic insertion of the pectoralis minor: implication in the arthroscopic treatment of shoulder stiffness

Abstract: Although ectopic insertion of the pectoralis minor has been previously described in the literature, the role of such anatomical variations in producing shoulder symptoms (i.e., pain and/or stiffness) remains controversial. We describe here a case of shoulder stiffness in which an ectopic insertion of the pectoralis minor over the supraspinatus tendon was found to be the main reason for severe contracture in external rotation and anterior thoracic pain. During arthroscopy, external rotation could not be restore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…One small series found an increased prevalence of superior labrum anterior posterior lesions in patients with this variant, thought to be due to inferior subluxation of the shoulder or instability of the biceps tendon, both of which may theoretically contribute to the development of a superior labrum anterior posterior lesion [14]. A single case report discusses the potential role of this variant in limiting external rotation in patients with adhesive capsulitis [15]. However, any effect on shoulder stability or range of motion is speculative given the small number of patients studied.…”
Section: Variant Attachment Site Of the Pectoralis Minor Tendonmentioning
confidence: 99%
“…One small series found an increased prevalence of superior labrum anterior posterior lesions in patients with this variant, thought to be due to inferior subluxation of the shoulder or instability of the biceps tendon, both of which may theoretically contribute to the development of a superior labrum anterior posterior lesion [14]. A single case report discusses the potential role of this variant in limiting external rotation in patients with adhesive capsulitis [15]. However, any effect on shoulder stability or range of motion is speculative given the small number of patients studied.…”
Section: Variant Attachment Site Of the Pectoralis Minor Tendonmentioning
confidence: 99%
“…2 However, Moineau et al reported that an ectopic insertion of the pectoralis minor was found to be the main reason for severe contracture in external rotation in shoulder stiffness. 4 In their arthroscopic finding, abnormal tendon insertion was under tension when the shoulder was externally rotated. Complete restoration of the passive external rotation was obtained only after complete release of the pectoralis minor from the supraspinatus.…”
Section: Discussionmentioning
confidence: 99%
“…5 Actually, these anatomic anomalies are not uncommon 2 and have also been reported by some authors as an incidental finding encountered during cadaveric dissection or surgical procedure. 1,3,4,8,10 However, its clinical significance in shoulder still remains obscure and the role can be debated. Further investigations are warranted to have clear impact on the shoulder function.…”
Section: Introductionmentioning
confidence: 99%
“…Yoo et al 18 recently reported that tendinous insertion of the pectoralis minor prohibited the retracted supraspinatus tendon from mobilization during arthroscopic rotator repair and gave rise to tension on the repaired cuff tendon. Other authors have reported that this variation was associated with coracoid impingement syndrome, 3 shoulder stiffness, 11 or superior labral lesion. 10 Previous reports are sparse, however, because they were only based on a single case or a small series of patients, and thus provide scant information specifically regarding its clinical relevance.…”
mentioning
confidence: 87%
“…14 This anomalous insertion of the pectoralis minor muscle has been reported as an incidental finding encountered during cadaveric dissection or surgeries. 3,8,11,15 The variation has been named differently in the literature, such as unusual attachment, ectopic insertion, tendinous insertion, or insertional variations of the pectoralis minor muscle. However, it is surprisingly common.…”
mentioning
confidence: 99%